The Profile of West Sumatera Volleyball Tarkam Player - Muhamad Sazeli Rifki; Ariando Ariston (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
The research problem is the unknown profile of West Sumatra volleyball tarkam players related to the contract process, tariffs, facilities, insurance and motivation. This study aims to determine the profile of West Sumatra volleyball tarkam players consisting of the contract process, tariffs, facilities, insurance and motivation. This type of research is descriptive research. The population in this study were West Sumatra volleyball tarkam players totalling 36 players consisting of 26 men and 10 women. The sampling technique in this study used the Total Sampling technique, so the sample in this study was 36 players consisting of 26 men and 10 women. The instrument in this study used a questionnaire. Data analysis and hypothesis testing used descriptive quantitative statistical formulas. From the data analysis, the results obtained the profile of the West Sumatra volley ball tarkam Player which consists of the contract process, tariffs, facilities, insurance and motivation is in the sufficient category.